2021
DOI: 10.3892/etm.2021.10214
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 alleviates lipopolysaccharide‑induced neuronal damage by inhibiting NLRP1 inflammasomes in HT22 cells

Abstract: Lipopolysaccharide (LPS) is a toxic component of cell walls of Gram-negative bacteria that are widely present in gastrointestinal tracts. Increasing evidence showed that LPS plays important roles in the pathogeneses of neurodegenerative disorders, such as Alzheimer's disease (AD). NADPH oxidase s2 (NOX2) is a complex membrane protein that contributes to the production of reactive oxygen species (ROS) in several neurological diseases. The NLRP1 inflammasome can be activated in response to an accumulation of ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In conclusion, although the mechanism by which Rg1 inhibits cell apoptosis has been widely reported ( 39 41 ), to the best of the authors' knowledge, the present study was the first to report that Rg1 exerted an anti-steatotic effect on hepatocyte apoptosis by downregulating a key enzyme, SGPL1, in the sphingosine signaling pathway ( Fig. 5 ).…”
Section: Discussionmentioning
confidence: 51%
“…In conclusion, although the mechanism by which Rg1 inhibits cell apoptosis has been widely reported ( 39 41 ), to the best of the authors' knowledge, the present study was the first to report that Rg1 exerted an anti-steatotic effect on hepatocyte apoptosis by downregulating a key enzyme, SGPL1, in the sphingosine signaling pathway ( Fig. 5 ).…”
Section: Discussionmentioning
confidence: 51%
“…These data demonstrated that rg1 may alleviate aβ deposition and learning and memory impairments through inhibiting neuroinflammation. A recent study by the authors suggested that rg1 treatment could improve lPS-induced neuronal injuries by downregulating the expression levels of nlrP1 inflammasomes in HT22 cells (58). Therefore, it was hypothesized that rg1 may delay the progression of AD by inhibiting NLRP1 inflammasome in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…BNCC337616), obtained from BeNa Culture Collection, were cultured in DMEM supplemented with 10% FBS (Gibco; Thermo Fisher Scientific, Inc.) and 1% penicillin/streptomycin in a humidified incubator with 5% CO 2 at 37˚C. HUVECs were treated with different concentrations of Rg1 (1, 5 or 10 µM; Shanghai YaJi Biotechnology Co., Ltd.) for 24 h at 37˚C ( 18 , 19 ). The AMP-activated protein kinase (AMPK) inhibitor compound C (CC; 5 mM; MilliporeSigma) was used to pretreat HUVECs for 2 h at 37˚C.…”
Section: Methodsmentioning
confidence: 99%